An experimental investigation on surface morphology of machined brass reinforced epoxy composite. (February 2014) - Ahmadi, Naeim E; Ansari, MNM; Zare, Ali; Rao, G Harii Krishna
This paper focuses on surface morphology of machined brass reinforced epoxy composite with different particle sizes in computer numerical control (CNC) milling process. Morphological studies in this research contain composite's surface roughness and dispersion of brass particles. Surface roughness is a proper criterion for predicting the performance of machining parameters and the quality of products. In this experiment, cutting parameters evaluated are feedrate, spindle speed, and depth of cut. Scanning electron microscope (SEM) and surface roughness measurement are carried out to study the major changes in texture of the machined surface and determine the optimal mixed-level array of cutting parameters. The results indicate that these parameters have significant effects on surface roughness. In the other word, a better surface quality can be obtained by varying the level of cutting parameters. In addition, it is concluded that a better surface roughness would be achieved by using the smallest size of brass particles.